RAB2A controls MT1‐MMP endocytic and E‐cadherin polarized Golgi trafficking to promote invasive breast cancer programs. (2nd June 2016) - Kajiho, Hiroaki; Kajiho, Yuko; Frittoli, Emanuela; Confalonieri, Stefano; Bertalot, Giovanni; Viale, Giuseppe; Di Fiore, Pier Paolo; Oldani, Amanda; Garre, Massimiliano; Beznoussenko, Galina V; Palamidessi, Andrea; Vecchi, Manuela; et al.
Abstract: The mechanisms of tumor cell dissemination and the contribution of membrane trafficking in this process are poorly understood. Through a functional siRNA screening of human RAB GTPases, we found that RAB2A, a protein essential for ER‐to‐Golgi transport, is critical in promoting proteolytic activity and 3D invasiveness of breast cancer (BC) cell lines. Remarkably, RAB2A is amplified and elevated in human BC and is a powerful and independent predictor of disease recurrence in BC patients. Mechanistically, RAB2A acts at two independent trafficking steps. Firstly, by interacting with VPS39, a key component of the late endosomal HOPS complex, it controls post‐endocytic trafficking of membrane‐bound MT1‐MMP, an essential metalloprotease for matrix remodeling and invasion. Secondly, it further regulates Golgi transport of E‐cadherin, ultimately controlling junctional stability, cell compaction, and tumor invasiveness. Thus, RAB2A is a novel trafficking determinant essential for regulation of a mesenchymal invasive program of BC dissemination. Synopsis: RAB2A is a novel trafficking determinant essential for the acquisition of a mesenchymal invasive program of BC dissemination. RAB2A acts by controlling both post‐endocytic trafficking of MT1‐MMP and Golgi transport of E‐cadherin. RAB2A is elevated in human BC and is a powerful and independent predictor of disease recurrence in BC patients. RAB2A promotes pericellular proteolysis by controlling late endosomal trafficking of MT1‐MMP through interaction with the homotypic fusion and protein sorting (HOPS)‐tethering complex component VPS39. RAB2A regulates Golgi transport of E‐cadherin and controls junctional stability, cell compaction and tumor invasiveness. Abstract : RAB2A is a novel trafficking determinant essential for the acquisition of a mesenchymal invasive program during breast cancer dissemination. RAB2A acts by controlling both post‐endocytic trafficking of MT1‐MMP and Golgi transport of E‐cadherin.